Volo Papale - Nowakowski, Tadeusz (Londyn : Polska Fundacja Kulturalna, 1982)
A recounting of the various trips of Pope John Paul II to several countries over the years.
Keywords: John Paul -- II, -- Pope, -- 1920-2005 -- Travel